Norepinephrine transporter blocker atomoxetine increases salivary alpha amylase - Warren, Christopher M.; Brink, Ruud L. van den; Bosch, Jos A. (Psychoneuroendocrinology, 2017)
It has been suggested that central norepinephrine (NE) activity may be inferred from increases in salivary alpha-amylase (SAA), but data in favor of this proposition are limited. We administered 40mg of atomoxetine, a selective NE transporter blocker that increases central NE levels, to 24 healthy adult participants in a double-blind, placebo-controlled cross-over design. Atomoxetine administration significantly increased SAA secretion and concentrations at 75-180min after treatment (more than doubling baseline levels). Consistent with evidence that elevation in central NE is a co-determinant of hypothalamic-pituitary-adrenal axis activity, salivary cortisol also approximately doubled at the same time points. Moreover, changes in salivary cortisol positively correlated with SAA (0.44<rho<0.56), bolstering the position that the origin of the changes in SAA reflect central NE. This work points toward the potential value of SAA as an inexpensive and non-invasive procedure to obtain information about activation of the central NE system.
Gesehen am 28.11.2018